1990
DOI: 10.1128/jvi.64.3.1086-1092.1990
|View full text |Cite
|
Sign up to set email alerts
|

Simian immunodeficiency viruses from African green monkeys display unusual genetic diversity

Abstract: African green monkeys are asymptomatic carriers of simian immunodeficiency viruses (SIV), commonly called SIVagm. As many as 50% of African green monkeys in the wild may be SIV seropositive. This high seroprevalence rate and the potential for genetic variation of lentiviruses suggested to us that African green monkeys may harbor widely differing genotypes of SIVagm. To investigate this hypothesis, we determined the entire nucleotide sequence of an infectious proviral molecular clone of SIVagm (155-4) and parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
61
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 36 publications
6
61
0
Order By: Relevance
“…To identify viral characteristics that may explain how the SIVs have successfully infected other primate species, we analyzed the types and extent of SIVsm diversification in naturally infected SMs. Our findings of high intra-host extremes of SIVsm V1V2 nt diversity extend previous studies of naturally SIV-infected SMs and African green monkeys (AGMs) [56][57][58][59][60][61][62][63] by demonstrating that viruses found within a single animal can vary by greater than 35% at the aa level. The ranges of aa diversity in some intra-host pairwise SIVsm V1V2 sequence comparisons in this study rival that of inter-animal comparisons [40].…”
Section: Discussionsupporting
confidence: 85%
“…To identify viral characteristics that may explain how the SIVs have successfully infected other primate species, we analyzed the types and extent of SIVsm diversification in naturally infected SMs. Our findings of high intra-host extremes of SIVsm V1V2 nt diversity extend previous studies of naturally SIV-infected SMs and African green monkeys (AGMs) [56][57][58][59][60][61][62][63] by demonstrating that viruses found within a single animal can vary by greater than 35% at the aa level. The ranges of aa diversity in some intra-host pairwise SIVsm V1V2 sequence comparisons in this study rival that of inter-animal comparisons [40].…”
Section: Discussionsupporting
confidence: 85%
“…More precisely, considering species-specific divergence, the degrees of identity between the two viruses and viruses from vervet (strains 155, TYO, and 3) or grivet (strain 677) monkeys were lower than those between viruses from vervet and grivet monkeys (52, 69, and 46% on average for the same proteins, respectively). Moreover, this homology is quite similar to that between SIVagm (strain 155) and sooty mangabey (Cercocebus atys) virus (sm H4) (28). In contrast, comparisons with another virus (sab-1) isolated from a sabaeus monkey (27) revealed high levels of amino acid identity (72, 90, and 80% on average for the Tat, Vpr, and Rev proteins, respectively).…”
Section: Comparisons Between Regulatory Proteins Of D30 and D42 Straisupporting
confidence: 55%
“…Distinct viruses have been identified from several different African simian species since the initial isolation of SIV from immunodeficient captive Asian macaques (SIVmac) (5). Five subgroups of primate viruses have been characterized according to sequence data: HIV-1 and SIVcpz (25,40); HIV-2, SIVmac, and SIVsm (24); SIVmnd (47); SIVsyk (22); and SIVagm (6,28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This variability poses a tremendous problem for the development of a therapy for AIDS. On the other hand, Johnson et al (1990) reported the gag gene was significantly more conserved than the env gene, and Weber et al (1987) showed a correlation between the decline of antibodies to gag p24 and clinical condition from asymptomatic to symptomatic phase. The use of cores instead of envelope proteins might be able to form part of the solution to this problem.…”
Section: Discussionmentioning
confidence: 99%